Throughput comparison of CDM and TDM for downlink packet transmission in CDMA systems with a limited data rate set. - Jaeweon Cho (IEEE Transactions on wireless communications)
Throughputs with code-division multiplexing (CDM) and time-division multiplexing (TDM) for downlink packet transmission are compared in multirate code-division multiple access (CDMA) systems. The authors propose and use a model that can show the impact of self-interference on the received bit energy per noise and interference power density (Eb/Nt). The developed analytical method reflects the effect of a limited data rate set, shadowed radio paths, and a limited number of spreading codes. Performance measures include asymptotic throughput, outage probability, probability of the data rate being limited by the given rate set, and probability of the system throughput being limited by the available number of spreading codes. The system throughput of packet channels for delay-tolerant service is evaluated in a 3GPP WCDMA system model. The authors show that the throughput with CDM can be equal to that with TDM in a fully loaded system without the data rate limitation. It is also shown that CDM can outperform TDM with respect to the asymptotic throughput when one takes into account the self-interference, the limitation on the data rate set, and resource reallocation of users in outage.